The land where the great encyclopedist Abu Rayhan Beruni was born - Nozima Jumayeva (Periodica Journal, 2024)
This article is about the life and scientific heritage of the famous encyclopedist Abu Rayhan Beruni, as well as the historical and cultural heritage of Beruni District, the place where he was born and grew up, and where he realized his huge astronomical size, places,historical facts related to the places are given.
Keywords: Rayhan Beruni; city of Kat; ancient Khorezm